Expression of cyclin D1 and cyclin E in human gastric carcinoma and its clinicopathologic significance. - Ahn, M. J. (Korean Academy of Medical Sciences, 1998)
Cyclin D1 and cyclin E are the mammalian G1 cydins that are both required and rate limiting for entry into S phase. Alterations in cell cycle regulators and subsequent deregulation of the cell cycle are frequently involved in tumorigenesis and/or tumor progression. We investigated the expression of cyclin D1 and cyclin E protein in 84 gastric carcinoma by immunohistochemical staining and also the relevance of each cyclin expression to the clinical outcomes. Overexpression of cyclin D1 and cyclin E was noted in 21 of 84 (25.0%) and 34 of 84 (40.5%) gastric cancer tissues, respectively. There was a significant correlation between overexpression of cyclin E and lymph node metastasis (p=0.003), recurrence (p=0.043), disease free survival (p=0.0378) and overall survival (p=0.0319), but no correlation was noted between overexpression of cyclin D1 and other clinicopathologic variables. These findings suggest that overexpression of cyclin E and cyclin D1 is a frequent finding in gastric cancer and immunohistochemical analysis for cell cycle regulators, especially cyclin E might be a useful prognostic indicator in gastric cancer.